(untitled) (Research, Society and Development, 2023)
Introduction. Oral dysfunction in older adults is caused by different physiological changes in the oral cavity due to aging and systemic diseases, as well as some alterations related to predisposing factors such as smoking, alcoholism, dehydration, and malnutrition. Decreased muscle tone and tongue mobility cause difficulties in chewing, swallowing, and speaking correctly, which affects the self-esteem and nutrition of the older adult. Objectives. To know which are the most common lingual alterations in older adults. Methodology. This article is a literature review to analyze the most common lingual disorders in older adults, describing their concept, prevalence, clinical characteristics, etiology, and treatment in the lingual organ. Conclusion. This study showed that the different lingual disorders are associated with aging, systemic diseases, and external factors. Therefore, the dentist must be trained to detect and treat these disorders and educate patients and caregivers about the importance of oral and lingual care in older adults.